2017
DOI: 10.1080/00016489.2016.1271449
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of electrode fold-over in cochlear implant surgery when using a flexible and slim perimodiolar electrode array

Abstract: A perimodiolar position can be achieved with the new CI532 electrode array. The new electrode also seems to be reliable for atraumatic intracochlear placement in scala tympani (ST).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…In their study, the electrode to modiolus distance was evaluated using CT. As in our study, advancing the CI532 electrode array past the first white marker position into the cochlea opening was undesirable, as it does not result in greater total insertion depths and only serves to increase the insertion depth of the first electrode contact and move basal electrodes away from the modiolus [16]. Ramos-Macías et al also evaluated electrode to modiolus distance using CT and demonstrated that it was constant in all electrode arrays and less than 0.3 mm [18]. Unfortunately, the pull-back technique was not performed in either of the studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In their study, the electrode to modiolus distance was evaluated using CT. As in our study, advancing the CI532 electrode array past the first white marker position into the cochlea opening was undesirable, as it does not result in greater total insertion depths and only serves to increase the insertion depth of the first electrode contact and move basal electrodes away from the modiolus [16]. Ramos-Macías et al also evaluated electrode to modiolus distance using CT and demonstrated that it was constant in all electrode arrays and less than 0.3 mm [18]. Unfortunately, the pull-back technique was not performed in either of the studies.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, preformed electrode arrays are fabricated in a spiral configuration and adjusted to the human cochlea's modiolar area. These electrode arrays were designed for intracochlear placement next to the modiolus [18]. This position leads to a narrower electric stimulation, a lower current spread to the adjacent neural population, a lower channel interaction, and a reduced risk of facial nerve stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tip fold-over may have an occurrence rate of 1.5% and usually occurs with flexible and slim perimodiolar electrodes [ 63 , 66 , 67 ]. Fold-over in the cochlea may lead to the rupture of the basilar membrane.…”
Section: Post-operative Imagingmentioning
confidence: 99%
“…This problem, referred to as tip fold-over or roll-over, occurs when the tip of the electrode array impinges the modiolar wall or other structure and is temporarily held stationary. In such a situation, further pushing of the array results in more electrodes advancing past it (Dhanasingh & Jolly, 2019), (Ramos-Macias et al, 2017). It can cause the patient to suffer from various post-operative complications, including reduced speech comprehension (Wanna et al, 2014), vertigo, pitch confusion and tinnitus (Dhanasingh & Jolly, 2019), and even cause injury to important adjacent neurovascular structures (Ying et al, 2013).…”
Section: Introductionmentioning
confidence: 99%